Ferroquine and artesunate in African adults and children with Plasmodium falciparum malaria: a phase 2, multicentre, randomised, double-blind, dose-ranging, non-inferiority study. Issue 12 (December 2015) - Held, Jana; Supan, Christian; Salazar, Carmen L O; Tinto, Halidou; Bonkian, Léa N; Nahum, Alain; Moulero, Bancole; Sié, Ali; Coulibaly, Boubacar; Sirima, Sodiomon B; Siribie, Mohamadou; Otsyula, Nekoye; et al.
Summary: Background: Artemisinin-based combination therapies (ACTs) are the recommended first-line treatment for uncomplicated Plasmodium falciparum malaria. Ferroquine is a new combination partner for fast-acting ACTs such as artesunate. We aimed to assess different doses of ferroquine in combination with artesunate against uncomplicated P falciparum malaria in a heterogeneous population in Africa. Methods: We did a phase 2, multicentre, parallel-group, double-blind, randomised, dose-ranging non-inferiority trial at eight African hospitals (two in Gabon, three in Burkina Faso, one in Benin, and two in Kenya). We recruited patients presenting with acute P falciparum monoinfection (1000–200 000 parasites per μL), and a central body temperature of at least 37·5°C or history of fever in the past 24 h. We assessed patients in two sequential cohorts: cohort 1 contained adults (bodyweight >50 kg) and adolescents (aged ≥14 years, >30 kg), and cohort 2 contained children (aged 2–13 years, 15–30 kg). We randomly assigned patients (1:1:1:1) to receive artesunate 4 mg/kg per day plus ferroquine 2 mg/kg, 4 mg/kg, or 6 mg/kg, given double-blind once per day for 3 days, or ferroquine monotherapy 4 mg/kg per day given single-blind (ie, allocation was only masked from the patient) once per day for 3 days. We did 14 patient visits (screening, 3 treatment days and 48 h post-treatment surveillance, a visit on day 7, then one follow-up visit per week until day 63). The primary endpoint was non-inferiority of treatment in terms of PCR-corrected cure rate against a reference value of 90%, with a 10% non-inferiority margin, assessed in patients treated without major protocol deviations for parasitologically confirmed malaria. We assessed safety in all treated patients. This study is registered withClinicalTrials.gov, numberNCT00988507, and is closed. Findings: Between Oct 16, 2009, and Sept 22, 2010, we randomly assigned 326 eligible patients to treatment groups, with last follow-up visit on Dec 1, 2010. 284 patients (87%) were available for per-protocol analyses. At day 28, PCR-confirmed cure was noted in 68 (97%, 95% CI 90–100) of 70 patients treated with ferroquine 2 mg/kg plus artesunate, 73 (99%, 93–100) of 74 with ferroquine 4 mg/kg plus artesunate, 71 (99%, 93–100) of 72 with ferroquine 6 mg/kg plus artesunate, and 54 (79%, 68–88) of 68 with ferroquine 4 mg/kg monotherapy. The three dose groups of ferroquine plus artesunate met the non-inferiority hypothesis. The most common adverse events were headache in cohort 1 (30 [19%] of 162 patients) and worsening malaria in cohort 2 (23 [14%] of 164 patients); occurrences were similar between treatment groups. Interpretation: Ferroquine combined with artesunate was associated with high cure rates and was safe at all doses tested, and could be a promising new drug combination for the treatment of P falciparum malaria. Ferroquine could also partner other drugs to establish a new generation of antimalarial combinations, especially in regions that have developed resistance to ACTs. Funding: Sanofi.